A cross sectional study regarding awareness of HIV/AIDS and practices of condoms among slum dwellers of Ajmer, Rajasthan, India - Meharda, Bharat; Sharma, Sanjeev Kumar; Keswani, Mahesh; Sharma, Rakesh Kumar (International Journal of Research in Medical Sciences, 2019)
Background: People living in slums are often deprived of health-care facilities and it make them vulnerable to infection like HIV/AIDS. Health education and behavioural changes is pivotal for prevention of HIV and HIV-related stigma. Methods: It was community based cross sectional study carried among 288 slum dwellers of Ajmer, Rajasthan, India. Results: Out of 288 study subjects (male and females in the group of 15-54 years) 144 (50%) males and 144 (50%) females. Out of 288 study subjects 278 (96.53%) were heard about HIV/AIDS. Out of 249 study subject who were aware about condom, 107 (42.97%) study subjects [74 (56.06%) male and 33 (28.21%) female] were presently using of condom. out of 278 study subject who had ever heard about HIV/AIDS majority 215 (77.34%) subjects got the information regarding HIV/AIDS through TV/cinema Conclusions: Present study shows that the study subjects of slums at Ajmer has inadequate awareness regarding the HIV/AIDS and poor practice of condoms.